Efficacy of prophylactic intravenous ondansetron for attenuation of pain on propofol injection (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Propofol is a popular intravenous anesthetic agent. One disadvantage of propofol is pain on its injection which can be excruciating at times. Various agents and methods have been tried to attenuate this unpleasant effect. Ondansetron, primarily used as an antiemetic has also been studied to reduce it.Methods: This randomized, prospective, double-blinded, placebo-controlled study was conducted on patients of either sex, American Society of Anesthesiologists (ASA) physical status I & II, undergoing elective surgeries requiring general anesthesia. The patients were randomly divided into ondansetron (A, received intravenous ondansetron 4 mg) and placebo (B, received equivalent volume of normal saline) groups. Manual occlusion of venous drainage was done at mid-arm by an assistant for 1 minute after which 25% of the calculated dose (2 mg/kg) of propofol (1% w/v in lipid base) was injected. Patients were asked by a blinded investigator to score the pain on injection of propofol on 4-point scale: 0=no pain, 1=mild pain, 2=moderate pain, 3=severe pain and compared in between two groups. The p